If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2.3 = x + -107 Reorder the terms: -2.3 + 2x = x + -107 Reorder the terms: -2.3 + 2x = -107 + x Solving -2.3 + 2x = -107 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2.3 + 2x + -1x = -107 + x + -1x Combine like terms: 2x + -1x = 1x -2.3 + 1x = -107 + x + -1x Combine like terms: x + -1x = 0 -2.3 + 1x = -107 + 0 -2.3 + 1x = -107 Add '2.3' to each side of the equation. -2.3 + 2.3 + 1x = -107 + 2.3 Combine like terms: -2.3 + 2.3 = 0.0 0.0 + 1x = -107 + 2.3 1x = -107 + 2.3 Combine like terms: -107 + 2.3 = -104.7 1x = -104.7 Divide each side by '1'. x = -104.7 Simplifying x = -104.7
| 8x+3.5=-7x+-2.1 | | 5(4x+7)=15 | | 0=2(n/5)-6(4n-2) | | a^4+2a^3-a^2-20= | | x-(0.06*x)=50000 | | 8/3x3 | | m^6-729= | | -3(4x+9)=-171 | | (8/3)(3) | | 1-2a^3+a^6= | | y=-3x+45 | | 6(8-7x)=6 | | pq+5=13forp | | 99.2/6.2 | | y=3x-45 | | t=3(3a+4)(3a+4) | | -5(-6x+9)=255 | | (6p-24)+9=23 | | 20-x=6x+6 | | a^2x^3-a^2y^3+2ax^3-2ay^3= | | 3(-2x-6)=-78 | | 4x+3.4=5x-1.1 | | -2x-2x=16 | | 18y+2=29 | | x-9=19+2 | | 11x+7.5=90 | | 2.3y-5.18=51.9 | | x-9=19+z | | -7+6x-7x=-11 | | 3x^2+2+-4x^3-x= | | a^4-25a^2+144= | | 4.5x=3(x+27) |